News in surgery of patients with early breast cancer. (November 2019) - Montagna, Giacomo; Ritter, Mathilde; Weber, Walter P.
Abstract: One of the most important news occurring in axillary surgery since the last St. Gallen Conference in 2017 was the publication of confirmatory long-term follow-up data from several large multicenter phase III non-inferiority trials, which clearly showed that axillary dissection can no longer be considered standard practice in all node-positive patients. Several groups are currently investigating the most accurate method to reliably determine axillary pathologic complete response after neoadjuvant chemotherapy to omit axillary dissection in initially clinically node-positive patients. Concerning breast surgery, after publication of the broadly endorsed definition of "no ink on tumor" for negative margins, many groups have demonstrated the expected decrease in re-excision rates. More evidence is needed to evaluate the adequate margin width in the neoadjuvant setting, where an increased risk of local recurrence has been shown compared to the upfront surgery setting. Besides narrowing margins and local down-staging by neoadjuvant therapy, another potential way to increase breast conservation rates is eliminating multicentricity as a contraindication. This requires high-volume tumorectomy, which has been demonstrated to be oncologically safe in a large series of oncoplastic reduction mammoplasties. However, the beneficial impact of oncoplastic surgery on quality of life still needs to be confirmed. The Oncoplastic Breast Consortium (OPBC) is a rapidly growing global non-profit organization that is committed to identifying and prioritizing knowledge gaps in this field. Currently, the OPBC focuses on research projects that address the major heterogeneity in breast reconstruction practice after nipple-sparing mastectomy.